Chronomorphosyntax: an analysis of the re form and se forms in si clauses in the Siete Partidas: an analysis of the –re form and –se forms in si clauses in the Siete Partidas (Signifiances (Signifying), 2019)
The results of recent studies indicate that the Spanish –re form, also called the future subjunctive form, has specific uses in written Spanish legal texts (Author 2017a; Author in press). More specifically, when found in si clauses, the – re form and its alternatives are used as rhetorical or discourse tools.  These results contradict the findings of the Comisión para la modernización del lenguaje jurídico which recommends the suppression of the –re form (2011a :11). However, in order to understand the use of this form, a dynamic model of legal syntax is needed. In this article, we address this gap by applying Macchi’s (1998 :2005a ; 2008) theory of chronosyntax, especially as apply to poetry. Indeed, we find that written legal text and poetry put a similar importance on the signifiers of the text. However, legal texts specifically exploit morphology to structure law articles. For these reasons, we recommend that not only the chronosyntactic information, but also chronomorphosyntactic information be taken into account when analyzing written legal texts.